Medical Education in Afghanistan: Challenges and Policy Implications - Stanikzai, Muhammad Haroon; Shanawa, Samiullah; Karimkhil, Ahmad Taha; Dadras, Omid (Informa UK Limited, 2025)
Medical education is considered the backbone of future health systems. However, Afghanistan's medical education system is ill-equipped to deliver quality education in the medical training institutions. This article provides insights into existing challenges in the Afghan medical education system. These challenges include infrastructural constraints, substandard recruitment practices, poor learning environment, limited access to updated learning educational resources, shortage of skilled and qualified lecturers, inaccessibility to modern technology, and financial difficulties. This calls for strengthening the Afghan medical education system, highlighting the importance of creating a national policy framework to enhance education quality and ensure academic institutions' sustainability.